A sensitive assay for ZYAN1 in human whole blood and urine utilizing positive LC–MS/MS electrospray ionization. (May 2017) - Patel, Harilal; Soni, Krunal; Trivedi, Rucha; Heading, Heather; Geue, Jason; Kansagra, Kevinkumar; Gupta, Rahul J; Pandya, Vrajesh B; Srinivas, Nuggehally R; Patel, Pankaj R; Desai, Ranjit C
Aim : A sensitive LC–MS/MS method was developed and validated for estimation of ZYAN1 in human blood/urine.Methods : An analog internal standard IOX2 along with ZYAN1 was quantified using selective reaction monitoring in positive mode. The chromatographic separation was performed by gradient elution with C18 analytical column (3 µm, 50 mm × 2.0 mm) with 4-min run time using an acidified mobile phase consisting of ammonium formate and acetonitrile. Protein precipitation enabled extraction of analytes from diluted blood/urine.Results : Calibration curve of ZYAN1 was linear (2–5000 ng/ml). The recovery of ZYAN1 and IOX2 was between 87 and 104%. Interday and intraday accuracy and precision was found well within the acceptance criteria.Conclusion : The validated assay was applied for clinical pharmacokinetics of ZYAN1 in healthy volunteers.